##### Ad

related to: K

Log[b](4) =

**k**→ you**k**now that: Log[a](x) = Ln(x) / Ln(a) ← where a is...2 Answers · Science & Mathematics · 16/09/2020

y -

**k**= a * (x - h)^2 y - (-1) = a * (x - 3)^2 y + 1 = a * (x - 3)^2 y = 2 when x = 0 2...x - 3)^2 y = (1/3) * (x - 3)^2 - 1 Another possibility: x - h = a * (y -**k**)^2 x - 3 = a * (y - (-1))^2 x - 3 = a * (y + 1)^2 y = 2 when x = 0 0 - 3 = a * (2...2 Answers · Science & Mathematics · 10/09/2020

**K**. Come back and tell us everything then .7 Answers · Society & Culture · 19/09/2020

I'll assume n>1. For large values of x,

**k**^n becomes negligible compared to x^n and we get: y = Ax^n...1 Answers · Science & Mathematics · 13/09/2020

...as a shortcut, you can just figure out 'a', calculate f(a) and then solve for

**k**. Example: (2x^3 + 3x^2 + kx -3) / (2x+5) Looking at the linear factor...4 Answers · Science & Mathematics · 03/09/2020

... written in vertex form, // y = a(x-h)² +

**k**// where the vertex is (h,**k**) // To convert between the 2 equation ...4 Answers · Science & Mathematics · 09/09/2020

I wor

**k**the helpdes**k**in the IT department for a large asphalt and concrete company. I've been doing IT and business analyst-related wor**k**for the last 15 years or so. If I wasn't doing this, I'd probably be doing something...5 Answers · Entertainment & Music · 21/09/2020

...the point (2, -3) is on the graph then P(2) = -3 so, 2³ +

**k**(2)² + 5 = -3 Then, 8 + 4**k**+ 5 = -3 => 4**k**= -16 so,**k**= -4 ...2 Answers · Science & Mathematics · 03/09/2020

...s the case, there's a well-

**k**nown formula for the sum of the first K squares: 1 + 4 + 9 + 16 + ... +**k**^2 + ... + K ^2 = K ( K ...1 Answers · Science & Mathematics · 08/09/2020

...the masses and inversely proportional to the square of the distance. b. F =

**k***Q*q / d² so to get 64 times the force you could either (i) multiply...1 Answers · Science & Mathematics · 19/09/2020

##### Ad

related to: K